Andean integration with integrity: The legacy of Emilio Romero and the South American Church - Judd Zanon, Esteban (1999)
A retrospective look at the life and writings of the great Peruvian and Puno thinker Emilio Romero (1899-1994), whose centenary we celebrate this last year of the century and millennium, gives the opportunity to remember one of the great figures of one of the peak moments of the intellectual life of the country and the Puno region. Romero, like others of his generation, in which intellectuals such as José Carlos Mariátegui, José Antonio Encimas and Luis Valcárcel stood out, marked a current of thought of clear concern for the drama of a country in formation and in constant search for solutions and alternatives.